In vivo evaluation of bioactive PMMA-based bone cement with unchanged mechanical properties in a load-bearing model on rabbits. (July 2015) - Fottner, Andreas; Nies, Berthold; Kitanovic, Denis; Steinbrück, Arnd; Hausdorf, Jörg; Mayer-Wagner, Susanne; Pohl, Ulrich; Jansson, Volkmar
Polymethylmethacrylate-based bone cements are widely used for fixation of joint replacements. To improve the long-term outcome, bioactive bone cements are aspired to advance the bone–cement interface. This study evaluated the in vivo properties of a new polymethylmethacrylate-based bioactive bone cement with addition of amphiphilic phosphorylated 2-hydroxyethylmethacrylate. Previous in vitro studies confirmed bioactive properties in cell culture, as well as unchanged mechanical properties are tests according to ISO 5833:2002. Three different variations of the cement (polymethylmethacrylate + phosphorylated 2-hydroxyethylmethacrylate, polymethylmethacrylate + phosphorylated 2-hydroxyethylmethacrylate + CaCl2 and polymethylmethacrylate + phosphorylated 2-hydroxyethylmethacrylate + CaCl2 + Na2 CO3 ) were compared to conventional polymethylmethacrylate cement. To evaluate the properties under load-bearing conditions, a spacer prosthesis was implanted into the femoral diaphysis of 24 rabbits. Additionally, a cement plug was installed into the proximal tibia. After three months, polished sections with Giemsa surface staining were prepared. The bioactivity was determined using the bone affinity index. The sections showed a good osseointegration of the bioactive bone cement without cement cracks under load-bearing conditions. Regarding the bone affinity index, the bioactive bone cement revealed a significantly higher value in the proximal tibia (25.9–37.7%) and around the spacer prosthesis (36.8–58.9%) compared to the conventional polymethylmethacrylate cement (12.8–17.0%). The results confirm the in vivo bioactivity of this bone cement. The absence of cement cracks indicates a sufficient mechanical stability to fix prostheses with this bioactive cement, but for a final assessment long-term tests are necessary.